2009
DOI: 10.1063/1.3103329
|View full text |Cite
|
Sign up to set email alerts
|

Maximization of granular outflow by oblique exits and by obstacles

Abstract: We investigate experimentally the intermittent discharge of a granular medium out of an exit at the bottom of a vertically shaken box. Changing the orientation of the bottom shows that there exists an angle (around 20°–25° with respect to the horizontal) at which the mean discharge rate increases up to a factor 1.9, as compared to the rate with horizontal bottom. Furthermore, adjusting the diameter and the distance of a cylindrical obstacle above the exit on the (horizontal) bottom, allows to optimize the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…For a three dimensional hopper there exists a critical orifice width above which the system never jams [4] while no such limit exists for a two dimensional system which can jam for large enough orifice widths [5]. It has been shown that the output flow rate from a hopper can be increased as large as 10% by placing suitable inserts within at appropriate locations [6][7][8]. This also decreases the probability of jamming by about two orders of magnitude [9].…”
mentioning
confidence: 99%
“…For a three dimensional hopper there exists a critical orifice width above which the system never jams [4] while no such limit exists for a two dimensional system which can jam for large enough orifice widths [5]. It has been shown that the output flow rate from a hopper can be increased as large as 10% by placing suitable inserts within at appropriate locations [6][7][8]. This also decreases the probability of jamming by about two orders of magnitude [9].…”
mentioning
confidence: 99%
“…Instead, the placement of obstacles is usually aimed to improve the flow and to the reduction of undesirable wall stresses. Indeed, most of the studies about silos and obstacles are performed with such a large outlet size that clogging is practically impossible [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A practical solution that is commonly implemented to improve the flow in both scenarios, people escaping from a room and the discharge of a silo, is the placement of an obstacle (or insert) just before (or above) the exit [2,[12][13][14][15][16][17][18]. In the case of the silo discharge, selecting the right insert position and size has been proved to increase the flow rate up to 10% [17,18].…”
mentioning
confidence: 99%